Analysis of Inclusive Education Curriculum in Physical Education, Sports, and Health Subjects at Brajan Elementary School, Tamantirto, Yogyakarta - Nur Safitri, Erin; Putri Fatmawati, Dwi (JURNAL PENDIDIKAN, 2024)
This study aims to determine the implementation of the inclusive education curriculum related to learning planning, learning implementation, and learning assessment.  The study was conducted at Brajan Elementary School, Tamantirto in the 2023/2024 school year. This study used a qualitative method with observation, documentation, and interview techniques with three main respondents: class VI teachers, principals, and Physical Education, Sports, and Health (PJOK) teachers. The research findings show that the school has not prepared a PDBK Student Learning Profile, made adaptations or modifications related to the devices, or prepared an Individual Learning Program. This is because teachers do not yet know about preparing inclusive learning, teachers have never attended training, schools do not have GPK, lack adequate resources, and schools have not been involved or collaborated with related experts in preparing learning devices for PDBK.